Pattern of Bacteria and Its Susceptibility of Ventilator-Associated Pneumonia Patients in ICU at Dr. Hasan Sadikin General Hospital, Bandung - Achmad Faisal Jundi; Nurita Dian KSS; Yanti Mulyana (Althea Medical Journal, 2016)
Background: Incidence of ventilator-associated pneumonia (VAP) is common in intensive care unit (ICU). This pneumonia, becomes important due to its association to increased length of hospital stay, increased costs, and increased mortality. Irrational administration of antibiotics can lead to development of bacterial resistance. The objective of this study was to describe the pattern of bacteria and the susceptibility of VAP patients.Methods: A descriptive study was carried out to 10 medical records of VAP patients in the ICU at Dr. Hasan Sadikin General Hospital, Bandung in January–June 2014. Microbiological culture results and antibiotics susceptibility testing of patients’ sputum were identified and the collected data were analyzed in form of tables and percentages by using a computer program.Results: Out of 44 cultures taken from 10 patients with VAP, 43 cultures had microbiological findings. Gram negative bacteria were found in 90.6% cultures, the rests were Gram positive bacteria and fungi. The majority of findings were: Acinetobacter baumannii (41.9%), Pseudomonas aeruginosa (18.6%), andKlebsiella pneumoniae (16.9%). The laboratory test result showed varied degrees of antimicrobial resistance to antibiotics.Conclusions: Bacteria found in sputum cultures of ICU patient with VAP are mostly of Gram negative. The result of susceptibility testing of bacteria shows many of the bacteria have resistance to antibiotics in ICU at Dr. Hasan Sadikin General Hospital. [AMJ.2016;3(2):195–9]DOI: 10.15850/amj.v3n2.772